Stimulasi Reproduksi Aseksual Pada Stichopus horrens dan Stichopus vastus di Perairan Pulau Karimunjawa, Kabupaten Jepara - Hermawan, Hermawan; Widianingsih, Widianingsih; Hartati, Retno (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Sexual reproduction on trepang has many constraint than asexual reproduction, such as fertilization success relies on broodstock number in nature and water conditions as a habitat for trepang. Therefore, research on production of trepang seed in needed. The aim of this research were to stimulate and observe fission ability and regeneration of trepang S. horrens and S. vastus (Family Stichopodidae) as well as determine survival rate of individual fission results. This research was conducted during October–December 2011 using field experimental method and analyzed descriptively. Stimulaton fission on this study conducted by tying 1/3 of anterior part of trepang body using a rubber band. Result showed that S. horrens dan S. vastus can be stimulated by fission. In both species, smaller group showed easier and quicker fission, but large group has higher regeneration. Posterior parts of the both species of sea cucumbers succesfully formed a new mouth complex. Posterior parts have higher survival rate than anterior.